Narration, Memory, and the Construction of Self Fatna El Bouih’s Talk of Darkness as a Case Study - IDMOULID, Omar (International Journal of Language and Literary Studies, 2025)
This paper investigates the intricate interplay between Memory and Literature as two interconnected symbolic systems that significantly conjure up in their representational capacities. It posits that literature transcends its marginalization in contemporary discourses by asserting its pivotal role in preserving and articulating both personal and collective memories. Literature’s unique ability to transform historical events, cultural identities, and collective experiences into enduring textual forms underpins its capacity as a mnemonic medium. Drawing on Paul Ricoeur’s theory of mimesis and Astrid Erll’s studies on memory, the paper examines how literature, particularly autobiography, mediates the reconstruction of Self and Memory within the frameworks of time and power structures. The analysis delves into the dual capacity of literature as both a locus of memory and a framework for organizing disparate experiences into coherent narratives, emphasizing its role in identity construction. It critically engages with Dariush Shayegan’s concept of "double fascination," which highlights the dynamic correlation of past and present in collective memory, alongside Ricoeur’s tripartite model of mimesis that elucidates the narrative dimensions of memory. The article further critiques the tensions between individual and collective representations of memory, exploring how literature navigates these through emplotment and imaginative engagement with history. By foregrounding the relationship between time, narrative, and memory, the article underscores literature’s enduring relevance in preserving and interrogating cultural histories and identities, resisting homogenized narratives, and fostering a nuanced understanding of collective and individual consciousness. The article concludes by situating literature as a dynamic mediator that reshapes the past to resonate with present realities, thus contributing to both individual and collective consciousness in memory culture.